Printed circuits handbook - Coombs, Clyde F. (McGraw-Hill, 1996)
Continuously in print since 1966, this is the definitive reference on all aspects of the design, engineering, and manufacture of printed circuit boards (PCBs). Completely updated to reflect the many changes affecting the PCB and electronics industries since the publication of the previous edition. Of particular note is new material on the manufacture of PCBs, concurrent engineering, and computer-aided engineering techniques.